O estudo da empatia em Edith Stein: possibilidades de uma atenção clínica de orientação fenomenológica para a Psicologia - OLIVEIRA, Thayane Cristhine Amaral (2019)
The present dissertation aims to present the main elements of the description of empathy (Einfühlung) in Edith Stein. The phenomenologist demonstrates in her writings a strong relationship with the Phenomenology of Edmund Husserl. The theme of empathy is, in particular, one of the themes to which Edith Stein proposes an explanation through a methodological description based on operations originating from a phenomenological attitude. Thus, this dissertation intends initially to describe some conceptual formats presented by the literature on empathy; later, it intends to present the Husserlian Phenomenology for the understanding of the world in its intersubjectivity character; to present Edith Stein's phenomenological description of the essence of empathy, going through the analytic aspect of corporeality, often discussed by the author to understand the theme; finally, to show how the empathy as investigated by Edith Stein can predict clinical attention of a phenomenological orientation to Psychology. To achieve the objectives established by the research, the study has a qualitative-phenomenological character. A theoretical study on the fundamentals in dialogue of the authors' Phenomenology (Husserl and Edith Stein) was carried out as a research procedure. In a special way, Stein's (1917/2004) work "On the Problem of Empathy" was used as the main source of research for the evidences reached. It was perceived as an inherent need in the empirical analytic, a resumption by the investigation of the corporeity, fundamental dynamics for the effectiveness of empathy, besides the insertion of the psychic and spiritual dimensions for the understanding of the constitution of the human person. Empathy was evidenced as a peculiar experience that enables the recognition of the ego, that is, of the other self, not as a character of identity or possession of the experience of others, but as a sensitive movement of what the other suffers, expresses, lives and feels. The phenomenological foundations present in the description of empathy demonstrated possibilities of the professional action of the psychologist in the prediction of clinical attention, establishing an ethical gesture and welcoming the person. However, empathy is emphasized as a spontaneous experience, which does not constitute a property of psychology, since prior to any theorization empathy is revealed even implicitly in the everyday world.